Knowledge and adaptation strategies of coffee smallholders toward climate change: evidence from Tanjung Agung, Semende Darat Ulu - Asia Afriyani; Tuty Emilia Agustina; Aura Khalisya Putri Hsaa; Ratih Wijayanti; Ali Martinus (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
Coffee farming was highly vulnerable to the impacts of climate change. Exploring the strategies used by small farmers in Tanjung Agung Village has had a big impact on climate change. This study aimed to identify the level of knowledge, adaptation practices, and polyculture practices and types of shade trees used by coffee smallholders in facing climate change in Tanjung Agung Village, Semende Darat Ulu Regency. These strategies have made a significant difference. This study used a qualitative, survey-based approach. It also conducted data collection and analysis. This process was both simultaneous and cyclical coffee smallholders have noticed the effects of climate change in the last 1-2 years. Also, 35% of smallholders have known about climate change for the last 3-5 years. Coffee smallholders use indicators to predict climate change. These indicators include increased temperatures and shifts in the rainy and dry seasons. Water availability was also an indicator. Up to 90% of small farmers take steps to reduce climate change. These steps include using better types of coffee, planting trees for shade, and controlling how far apart the coffee plants were. Farmers also make air holes and use coffee bean skins to improve the soil. Our findings show that coffee smallholders understand climate change impacts well. They also quickly use strategies to adapt their crops to the changing climate. Smallholders use 16 types of shade crops as a strategy. The most widely used shade crops were petai, mango, avocado and durian.